2006
DOI: 10.1017/s0031182005009625
|View full text |Cite
|
Sign up to set email alerts
|

Comparative development of Echinococcus multilocularis in its definitive hosts

Abstract: The comparative development of Echinococcus multilocularis was studied in its definitive hosts, the fox, dog, cat and raccoon dog, beyond the pre-patent period to 90 days post-infection. All host species, apart from cats were susceptible to infection and capable of supporting substantial worm burdens. Although worms in cats matured and produced thick-shelled eggs, their overall development was retarded compared to that in other species in which the parasite matured rapidly producing large populations of gravid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 26 publications
1
48
0
3
Order By: Relevance
“…Unlike cats, in which infection is very limited , Thompson et al 2006, Umhang et al 2015, the dog is an adequate host for the development of the mature forms of E. multilocularis: the time and intensity of the excretion of tapeworm eggs by infected dogs were comparable to the results obtained for foxes and raccoon dogs .…”
mentioning
confidence: 72%
“…Unlike cats, in which infection is very limited , Thompson et al 2006, Umhang et al 2015, the dog is an adequate host for the development of the mature forms of E. multilocularis: the time and intensity of the excretion of tapeworm eggs by infected dogs were comparable to the results obtained for foxes and raccoon dogs .…”
mentioning
confidence: 72%
“…In contrast to the red fox, which is a native species, raccoon dogs were introduced from the Far East and are currently among the most common wild carnivores in Baltic countries (Kowalczyk, 2006). Recent experimental studies have shown that raccoon dogs are highly susceptible to intestinal E. multilocularis infections ; Thompson et al 2006). Natural helminth infections have also been documented in several studies in Europe (Machnicka-Rowinska et al 2002;Shimalov and Shimalov, 2002; Kirjušina, M. unpublished data in Bagrade et al 2008;Hurnikova et al 2009;Schwarz et al 2011).…”
Section: Introductionmentioning
confidence: 94%
“…In nature this zoonosis involves different mammalian hosts: carnivores ( (32), and a wide spectrum of rodents are intermediate hosts (34). Humans who are accidentally infected serve as intermediate hosts and may develop AE after a long incubation period (8,33).…”
mentioning
confidence: 99%